2014 IEEE Global Engineering Education Conference (EDUCON) 2014
DOI: 10.1109/educon.2014.6826167
|View full text |Cite
|
Sign up to set email alerts
|

Web accessibility evaluation of massive open online courses on Geographical Information Systems

Abstract: This paper describes some of the challenges that exist to make accessible massive open online courses (MOOCs) on Geographical Information Systems (GIS). These courses are known by the generic name of Geo-MOOCs. A MOOC is an online course that is open to the general public for free, which causes a massive registration. A GIS is a computer application that acquire, manipulate, manage, model and visualize geo-referenced data. The goal of a Geo-MOOC is to expand the culture of spatial thinking and the use of geogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 7 publications
1
11
0
1
Order By: Relevance
“…This type of study requires an assessment and monitoring of LCMS accessibility to guarantee the universal accessibility of this type of systems. Similar studies were conducted by [24], [25], and [26], among others.…”
Section: Related Worksupporting
confidence: 66%
“…This type of study requires an assessment and monitoring of LCMS accessibility to guarantee the universal accessibility of this type of systems. Similar studies were conducted by [24], [25], and [26], among others.…”
Section: Related Worksupporting
confidence: 66%
“…The existing relevant studies have sufficiently explained the general concepts of accessibility, disability, diversity, universal access as well as the demographics [22][23][24][25][26][27]29,30,33,35,38,[42][43][44]46,54,56,57,60,61]. In the same way, the Convention of the Rights of Persons with Disabilities [29,44,59] and related legislation had also been addressed, both in general [29,44,61] and countryspecific level, e.g.…”
Section: Moocs and The Characterization Of The Accessibility Problemmentioning
confidence: 99%
“…The existing relevant studies have made important efforts to identify the needs related mainly to blindness and low vision [27][28][29][30][31]35,45,48,53,57,59], deafness and reduced hearing [29,45,49,57], and combined disabilities due to natural aging [23,33,51,54].…”
Section: Moocs and The Identification Of Accessibility Needsmentioning
confidence: 99%
“…However, their openness does not necessarily equate an access, as studies have shown that most MOOC websites do not fulfill minimum accessibility requirements [5,6]. Hence, despite the MOOCs adage to include and offer education to all people, research has shown that their interface is not accessible to people with disabilities, such as the blind [7,8,9] or the elderly [10]. In spite of the opinions that in a single course MOOCs bring together diversity in ideas, cultures and regions, they currently exclude the disabled, which approximately comprise 15% of the world population [7].…”
Section: Related Workmentioning
confidence: 99%
“…Evaluators randomly selected a course and lectures from Almooc and made notes about the problems discovered. To evaluate Almooc's compatibility with assistive technologies, various screen reader software was used, such as: Non-visual Access Desktop (NVDA) 8 , WebAnywhere 9 , and ChromeVox 10 .…”
Section: Heuristic Evaluationmentioning
confidence: 99%